Exploring teacher talk in training classrooms: A case study at SD Linimasa, Kuningan - Lili Sururi Asipi; Dwi Nopiyadi (Concept : Community Concern for English Pedagogy and Teaching, 2023)
The aim of this study is to investigate the types of teacher talk and their meanings in dealing with diverse students. This research aimed to explore several fundamental aspects that occurred in classroom interaction. They are: 1) the types of teacher talk; 2) the most dominant and least performed type of teacher talk; and 3) the contribution of teacher talk to supporting learning. This research was a case study with the participation of three English teachers. The data had been collected through classroom observation, semi-structured interviews, and questionnaires. In examining the utterances uttered by all teachers, video recordings were utilised throughout the learning process. The result of the video transcription was then analysed using Moskowitz’s FLINT system to categorise the type of teacher talk. The result was then cross-checked with the interview and questionnaire to support the validity of the data. The study's findings demonstrated that during the teaching and learning process, teachers used nearly every kind of teacher discourse. Joking was the least frequent sort of speech, while asking questions was the most frequent. Through their utterances during the session, the teacher also provided support to the students who transferred from situations where English was not their first or second language. Teachers facing comparable situations may find it helpful to consider the study's implications and outcomes while trying to boost student engagement, which in turn encourages students to participate more actively in the learning process. Keywords: Exploration; classroom interaction; teachers’ talk;